Legal Protection for Online Transportation Service Providers in Transporting Passengers - Desak Nyoman Oxsi Selina; I Made Wirya Darma (Jurnal Hukum Prasada, 2021)
Transportation is one of the derivative needs in society due to economic, social activities, and so on. In general, there are two transportations, namely based on conventional and online, but the problem is that discrimination often occurs against providers of online-based transportation services, especially in transporting passengers. Thus, the purpose of this study is to find out the legal protection for online transportation service providers in transporting passengers and to find out the legal consequence of discriminating against online transportation service providers in carrying passengers. The method used in this study is normative legal research method. Meanwhile, the legislative and conceptual approach is the approach used in this study. The results of this study showed that the legal protection of online transportation service providers in Indonesia is regulated in legislation including the 1945 Constitution of the Republic of Indonesia which in principle every legal subject must be treated equally before the law, and Law Number 39 Year 1999 which protects that every person is entitled to a job, and legal protection is also contained in Law No. 8 of 1999 which in principle regulates the rights and obligations of business actors. The legal consequence of discrimination is that it can result in criminal and civil law in the form of compensation for imprisonment or fines.